콜린성 신경세포에서 Honokiol에 의한 Tau 단백질 인산화의 억제효과 - Le Nguyen, Mai Khoa (The Graduate School, Ajou University, 2011)
Hyperphosphorylation of tau protein and subsequent formation of neurofibrillary tangle is the main pathological feature observed in Alzheimer’s disease (AD) brain. One of the key enzymes which are responsible for hyperphosphorylation of tau is glycogen synthase kinase-3β (GSK3β). In this respect, inhibition of GSK3β activity has been considered as a therapeutic target for AD suppression or treatment. Here the inhibitory effects of honokiol, a major constituent isolated from the bark of Magnolia obovata Thunb, on tau hyperphosphorylation and cell death in cholinergic neuroblastoma cell lines were described. In LA-N2 cells, a human cell line, the effects of honokiol on tau abnormal phosphorylation under amyloid-beta (Aβ) exposure was primarily observed. In differentiated SN56.B5.G4 (SN56) cells, a mouse cell line, honokiol not only protected SN56 cells from Aβ-induced toxicity, but also ameliorated the Aβ-induced abnormal tau phosphorylation. In addition, it was observed that honokiol inhibited GSK3β activity in a dose-dependent manner, its effect as good as other well-known GSK3β inhibitors, alsterpaullone and lithium chloride. It was also found that honokiol promoted Akt activity, implying that Akt was involved in the effect of honokiol on GSK3β activity. Honokiol also inhibited cycline dependent protein kinase 5 (Cdk5) activity, which is another major kinase for hyperphosphorylation of tau. Taken together, these results suggest that honokiol may be a new potential natural compound that is relevant for the treatment of AD.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2011. 2
Keywords: 콜린성 신경세포; Tau 단백질 인산화